A multiplicity results for a singular problem involving the fractional p-Laplacian operator. Issue 9 (1st September 2016) - Ghanmi, A.; Saoudi, K.
Abstract : The purpose of this work is to study the following singular problem: where, be a bounded smooth domain, is a positive parameter, such that and where and r is the homogeneity degree of the function f . Under appropriate assumptions on the function f, we employ the method of Nehari manifold combined with the fibering maps in order to show the existence of such that for all, problem has at least two positives solutions.